Fe2O3 nanocluster-decorated graphene as O2 electrode for high energy Li–O2 batteries - Hoster, Harry E. (2013)
Fe2O3 nanocluster-decorated graphene (Fe2O3/graphene) hybrids with controlled contents of Fe2O3 were prepared by a facile electrochemical process. These Fe2O3/graphene hybrids were tested as O2 electrodes for Li–O2 batteries, which exhibited enhanced discharge capacities as compared to that of a pure graphene based O2 electrode, e.g. the Fe2O3/graphene electrode with 29.0 wt% of Fe2O3 delivered a discharge capacity of 8290 mA h g−1 and a round-trip efficiency of 65.9% as compared to 5100 mA h g−1 and 57.5% for a pure graphene electrode. The excellent electrochemical properties of Fe2O3/graphene as an O2 electrode is ascribed to the combination of the fast kinetics of electron transport provided by the graphene sheets and the high electrocatalytic activity for O2 reduction provided by the Fe2O3.